The Taliban : War, Religion and the New Order in Afghanistan - Marsden, Peter, 1945 September 22- (Karachi, Pakistan Oxford University Press, 1998)
The Taliban explores what the Taliban stand for and the factors leading to their rapid rise. It describes the war which continues to afflict the Afghan people as well as the geo-political context and part played by vertain powers in the region, and by the United States, in the Taliban's dramatic expansion.
Include Maps, Bibliography and Index
Keywords: Afghanistan -- Politics and government -- Taliban -- Islam and politics -- Islamic fundamentalism